Analyzing security threats and mitigation techniques for fog computing in IoT-enabled smart cities - Emon, Sheikh Sadi; Malek, Marium; Turja, Md. Iftekhar Hossain; Sun, Khalid Redwan; Rahman, Md. Atiqur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.